TEOLOGI MENGGUGAT SISTEM DEMOKRASI DAN POLITIK DI INDONESIA - Roni, Roni; Yosbekasa, Yosbekasa (Institut Agama Kristen Negeri Toraja, 2024)
Abstract: This article discusses the democratic and political system in Indonesia, which is not free from challenges such as corruption, money politics, human rights violations, and various other obstacles. These conditions indicate that Indonesian democracy has not reached its final stage. Various individuals and political elites, using the legitimacy of power, tarnish the democratic system in Indonesia, giving rise to various criticisms from democracy advocates to this day. Through this writing, the author attempts to examine the Indonesian democratic system through the lens of Jurgen Moltmann's political theology in Indonesia. This research uses a qualitative literature study approach to describe Moltmann's views regarding political theology within the democratic system in Indonesia. Abstrak: Artikel ini membahas sistem demokrasi dan politik di Indonesia yang tidak terbebas dari tantangan, seperti korupsi, money politik, pelanggaran Hak Asasi Manusia (HAM), dan berbagai macam tantangan lainnya. Kondisi tersebut menunjukkan bahwa demokrasi Indonesia belum sampai pada tahapan final. Berbagai macam oknum dan elit-elit politik dengan legitimasi kekuasaan mencoreng sistem demokrasi di Indonesia, sehingga timbul berbagai macam kritik dari pejuang demokrasi hingga saat ini. Melalui tulisan ini, penulis mencoba membaca sistem demokrasi Indonesia melalui lensa teologi politik Jurgen Moltmann di Indonesia. Penelitian ini menggunakan pendekatan kualitatif studi kepustakaan, untuk menguraikan bagaimana pandangan Moltmann terkait teologi politik dalam sistem demokrasi di Indonesia.